Establishing a coordination system for construction project organizations by simulating human body circulatory system - Shen, Fang-Ying; Chang, Andrew S. (Journal of Civil Engineering and Management, 2013)
Construction projects are highly fragmented with many participants and activities involved during construction, so coordination is complicated and critical for project organizations. The physiological functions of the human body such as the circulatory system are natural and effective. This study established a coordination system for construction projects by simulating the circulatory system to improve work effectiveness. The contractor has to coordinate the owner and suppliers, that is, like the heart does to the brain and various organs. A procedure was also developed and illustrated through a case study to use the system practically. The contractor engineer acting as a receptor evaluates coordination needs derived from project uncertainty and equivocality and collect time spent on coordination with various parties. Coordination time or amount is adjusted when coordination supply does not meet needs. This procedure can be applied on construction project organizations to plan and execute coordination work.